Qoraqalpogʻiston Respublikasi hududini shaharlarni barqaror rivojlantirish maqsadida tabiiy-xoʻjalik-urbanizatsiya tizimi boʻyicha rayonlashtirish - Tashtaeva, Saida Kakharovna; Khodjaeva, Gulya Ashirbaevna; Dauletbaueva, Dilbar Dastanovna (SCIENCE and SOCIETY, 2026)
The article analyzes the processes of urbanization of the Republic of Karakalpakstan and its territorial features, the territorial structure of cities and their place in the urban system of the republic. In order to ensure the sustainable development of the republicʻs cities, a three-dimensional assessment and integral zoning were carried out in accordance with the "nature-economy-urbanization" system, the values of the urbanization of the districts were substantiated, and scientific and practical recommendations on priority areas of sustainable urban development and urbanization were developed.
Keywords: city; urbanization; territory; integral zoning; natural conditions; ecological situation